1999
DOI: 10.1021/jp990838c
|View full text |Cite
|
Sign up to set email alerts
|

Quenching of Singlet Oxygen by Trolox C, Ascorbate, and Amino Acids:  Effects of pH and Temperature

Abstract: The pH dependence of singlet oxygen quenching by histidine, N-acetyltyrosine ethyl ester (ATEE), ascorbic acid, Trolox C, and tryptophan has been observed using time-resolved infrared luminescence measurements in a D2O/acetonitrile (50:50 v/v) solvent. Deprotonation of ascorbic acid, the protonated imidazole ring of histidine and the phenolic group of ATEE leads to an increase in the quenching rate constants by between 2 and 3 orders of magnitude. Such changes appear to be the basis for wide variations in quot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
93
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(108 citation statements)
references
References 27 publications
14
93
0
Order By: Relevance
“…In the present case, k r GA = 1.110 7 M -1 s -1 , a typical value for the reaction of aminoacid moieties with 1 O 2 (Michaeli & Feitelson, 1994;Bisby et al, 1999). By comparison with the total quenching rate constant, k t GA = 2.710 7 M -1 s -1 , it can be concluded that almost 60% of the interaction with 1 O 2 is through physical quenching and about 40% of the reactive moieties of GA are oxidized by 1 O 2 .…”
Section: Figure 1bmentioning
confidence: 58%
See 1 more Smart Citation
“…In the present case, k r GA = 1.110 7 M -1 s -1 , a typical value for the reaction of aminoacid moieties with 1 O 2 (Michaeli & Feitelson, 1994;Bisby et al, 1999). By comparison with the total quenching rate constant, k t GA = 2.710 7 M -1 s -1 , it can be concluded that almost 60% of the interaction with 1 O 2 is through physical quenching and about 40% of the reactive moieties of GA are oxidized by 1 O 2 .…”
Section: Figure 1bmentioning
confidence: 58%
“…In order to separate the contribution of physical and chemical quenching, we monitored the consumption of dissolved 3 O 2 by GA using a FOXY-R oxygen-sensitive luminescent sensor coupled with to CCD detector from OceanOptics, Figure 3a. The dye methylene blue was used as sensitizer (   0.52) and histidine as actinometer, since this aminoacid reacts completely with 1 O 2 with k r His = 4 10 7 M -1 s -1 , (Bisby et al, 1999).…”
Section: Figure 1bmentioning
confidence: 99%
“…Nevertheless, increased levels of protein expression (up to 50% higher expression by fluorescence intensity) were non-toxic and yielded similar results. The antioxidant Trolox was added as a quenching agent to further reduce the likelihood of off-target effects (Bisby et al, 1999). Trolox concentration and irradiation time and power were optimized using the Golgi-localized control construct to achieve bleaching without affecting Golgi HeLa cells stably expressing GalNacT2-GFP as a Golgi marker were transiently transfected with Killer Red constructs and, after 2 days, were placed in medium containing 375 mM Trolox.…”
Section: Targeted Acute Inactivation Blocks Er Exitmentioning
confidence: 99%
“…Singlet oxygen is a highly reactive, electrophilic species that reacts rapidly with electron-rich moieties, such as the double bonds of lipids [1,2], thiols [3,4], and ascorbate [5,6,7,8,9]. We have observed previously that in neutral solutions singlet oxygen reacts with ascorbate (AscH-) to produce H 2 O 2 [9].…”
Section: Introductionmentioning
confidence: 99%